Dynamic Modeling of Genes Controlling Cancer Stem Cell Proliferation - Wang, Zhong; Liu, Jingyuan; Wang, Jianxin; Wang, Yaqun; Wang, Ningtao; Li, Yao; Li, Runze; Wu, Rongling (Frontiers in Genetics, 2012)
The growing evidence that cancer originates from stem cells holds a great promise to eliminate this disease by designing specific drug therapies for removing cancer stem cells. Translation of this knowledge into predictive tests for the clinic is hampered due to the lack of methods to discriminate cancer stem cells from non-cancer stem cells. Here, we address this issue by describing a conceptual strategy for identifying the genetic origins of cancer stem cells. The strategy incorporates a high-dimensional group of differential equations that characterizes the proliferation, differentiation, and reprogramming of cancer stem cells in a dynamic cellular and molecular system. The deployment of robust mathematical models will help uncover and explain many still unknown aspects of cell behavior, tissue function, and network organization related to the formation and division of cancer stem cells. The statistical method developed allows biologically meaningful hypotheses about the genetic control mechanisms of carcinogenesis and metastasis to be tested in a quantitative manner.